Interpreting Gaze and Shame as Means of Grace and Divine Recognition: A Response to the Stigmatization of the Chinese Ethnicity in Indonesia - Layantara, Jessica Novia (Dialog, 2025)
As an ethnic minority, the Chinese community in Indonesia continues to face negative stigma. The Chinese ethnic group is often viewed as the source of economic inequality in the country. The May 1998 riots serve as evidence of the stigmatization and discrimination against the Chinese community. Even today, this stigmatization persists. This paper seeks to answer the question: How can philosophy and theology contribute to addressing the stigmatization of ethnic Chinese in Indonesia? The issue of stigmatization is analyzed using Jean-Paul Sartre and Frantz Fanon's theories of gaze and shame. These theories are then integrated with the theological views on gaze and shame presented by Philip D. Jamieson and Niel Gregersen. The results of the study suggest that the stigmatization of ethnic Chinese in Indonesia should not be met with arrogance or withdrawal, but rather: (1) Understood as a “means of grace,” not in accepting the stigma, but as an opportunity for dialogue and the construction of new narratives; (2) Rejected through the power of God's recognition, which enables the ethnic Chinese in Indonesia to engage in transformative dialogue that moves beyond the stigma.